NFYA promotes the anti-tumor effects of gluconeogenesis in hepatocellular carcinoma through the regulation of PCK1 expression - Tsujimoto, Goki; Ito, Rin; Yoshikawa, Kei; Ueki, Chihiro; Okada, Nobuhiro (Frontiers in Cell and Developmental Biology, 2022)
Reprogramming of glucose metabolism occurs in many human tumor types, and one of these, gluconeogenesis, is known to exhibit anti-tumor effects in hepatocellular carcinoma (HCC). The transcription factor NFYA regulates gluconeogenesis in the normal liver tissue, but the function of the NFYA-gluconeogenesis axis in cancer and the functional differences of NFYA splicing variants in the regulation of gluconeogenesis is still unclear. Here, we demonstrate that NFYAv2, the short-form variant, upregulates the transcription of a gluconeogenic enzyme PCK1. We further reveal that its regulation induces high ROS levels and energy crisis in HCC and promotes cell death. These indicate that the NFYAv2-gluconeogenesis axis has enhanced anti-tumor effects in HCC, suggesting that the axis may be a potential therapeutic target for HCC. Furthermore, Nfyav1-deficient mice, spontaneously overexpressing Nfyav2, had no increasing gluconeogenesis in the liver. Taken together, our results reveal NFYAv2-gluconeogenesis axis has anti-tumor effects and the potential for NFYAv2 to be a safer therapeutic target for HCC.